FORMULASI LULUR BODY SCRUB BERAS KETAN HITAM (ORYZA SATIVA VAR. GLUTINOSA) DENGAN PERPADUAN YOGURT SEBAGAI ZAT AKTIF - Agata, Shelly Dwi; Jayadi, Lukky (Jurnal Riset Kefarmasian Indonesia, 2022)
Scrub is a cosmetic preparation for skin care that functions as an abrasive in the form of scurb granules that can remove dead skin cells from the epidermis. The scrub used in this study was derived from black glutinous rice (Oryza Sativa Var. Glutinosa) which contains antioxidant components and can help activate vitamin B1 which helps maintain healthy skin and helps skin look brighter. In addition, the components of the active substance are also needed. Yogurt was chosen as the active ingredient of the preparation because it has Alpha Hydroxy Acid (AHA) which can help the exfoliation process and help remove dead skin cells and increase the skin's natural moisture factor. The purpose of making body scrub preparations using yogurt as an active substance with varying concentrations of 0%, 5%, 10% and 15%. This research was conducted experimentally. The physical quality test of the preparation includes organoleptic test, homogeneity test, pH test, adhesion test, dispersibility test, stability test, and emulsion type test. The results show that the preparations made meet the physical evaluation of the scrub preparations meet the quality requirements, meet the organoleptic quality evaluation, namely the formulation of the scrub preparations F0, F1, F2, and F3 with semi-solid texture, purplish gray color with a mixture of black glutinous rice and yogurt. Each preparation is homogeneous. Emulsion type o/w. pH ranged from 7, 45 - 6, 74. It complies with the quality requirements of the spreadability test and has good emulsion stability. The conclusion of this study is that the F3 formulation with the addition of 15% yogurt has the best physical quality in the organoleptic test, homogeneity test, pH test, dispersibility test, stability test, and emulsion type test.